Urban–rural differences in the relationship between stunting, preschool attendance, home learning support, and school readiness: A study in Côte d'Ivoire - Brou, Abenin Mathieu; Djalega, Franck Adjé; Tokpa, Venance; Seri, Edy Constant Gbala; Anoua, Apie Léa Fabienne; Robinson, Julie Ann (Frontiers in Public Health, 2023)
Background Stunted physical growth during early childhood is a marker of chronic undernutrition, and the adverse life circumstances that underlie it. These have the potential to disrupt normal brain development and the acquisition of foundational cognitive, language, social and motor skills. Stunting is prevalent in most low-and middle-income countries. Because the prevention of stunting requires large-scale structural and attitudinal changes, several psycho-educational interventions have been developed to mitigate the adverse association between early stunting and skill development. However, the resource-intensive nature of custom-designed interventions limit their sustainability and scalability in resource-limited settings. This study explored the possibility that available resources that promote positive development (existing preschool education programs, and no- or low-cost home-based learning activities and resources) may protect against any negative association between stunting and the acquisition of foundational skills required for academic learning and adaptation at school. Method Data for 36-to 59-month-old children (n = 3,522; M = 46.7 months; 51.2% male; 74.1% rural) were drawn from the most recent Multiple Indicator Cluster Survey conducted in Côte d'Ivoire (MICS5, 2016). Stunting was assessed using the WHO Child Growth Standards. Preschool attendance and home learning activities and resources were assessed by maternal report. School readiness was assessed using the 8-item form of the Early Child Development Index (ECDI). Results A high percentage of children met the criteria for stunting (28.5%; 19.7% moderate; 8.8% severe). There were marked urban–rural differences in the prevalence of stunting, rates of preschool attendance, home learning activities and resources, children's school readiness scores, and the relationships between stunting, the protective factors and school readiness scores. These urban–rural differences in ECDI scores could be fully explained by differences between these settings in stunting and the protective factors. However, only two protective factors (access to books and home-based activities that promote learning) made independent contributions to variance in ECDI scores. There was tentative evidence that stunted children whose homes provided highly diverse learning activities and multiple types of learning resources were more likely than those who did not to have a high level of school readiness. Conclusion Capitalizing on the existing practices of families that show positive deviance in caregiving may provide a basis for culturally appropriate, low-cost interventions to improve school readiness among children in low- and middle-income countries, including children with stunted growth.